(untitled) (Clinics, 2016)
OBJECTIVE: Adenotonsillectomy is recognized as an effective therapy for snoring and sleep disorders in children. It is important to understand whether adenotonsillectomy significantly increases the volume of the pharyngeal space. The goal of this study was to evaluate the change in oropharyngeal volume after adenotonsillectomy and the correlation of this change with the objective volume of the tonsils and body mass index. METHODS: We included 27 subjects (14 males) with snoring caused by tonsil and adenoid hypertrophy. The mean age of the subjects was 7.92 (±2.52) years. Children with craniofacial malformations or neuromuscular diseases or syndromes were excluded. The parents/caregivers answered an adapted questionnaire regarding sleep-disordered breathing. All patients were subjected to weight and height measurements and body mass index was calculated. The subjects underwent pharyngometry before and after adenotonsillectomy and the volume of both excised tonsils together was measured in cm3 in the operating room. RESULTS: Pharyngometric analysis showed that the mean pharyngeal volume was 28.63 (±5.57) cm3 before surgery and 31.23 (±6.76) cm3 after surgery; the volume of the oropharynx was significantly increased post-surgery (p=0.015, Wilcoxon test). No correlation was found between the objective tonsil volume and the post-surgical volume increase (p=0.6885). There was a fair correlation between the oropharyngeal volume and body mass index (p=0.0224). CONCLUSION: Adenotonsillectomy increases the volume of the pharyngeal space, but this increase does not correlate with the objective tonsil size. Furthermore, greater BMI was associated with a smaller increase in the pharyngeal volume. Oropharyngeal structures and craniofacial morphology may also play a role in the increase in oropharyngeal volume.